A conceptual framework of cool for social marketing. Issue 2 (11th April 2016) - Mohiuddin, Khondker Galib B.; Gordon, Ross; Magee, Christopher; Lee, Jeong Kyu
Abstract : Purpose: The purpose of this paper is to present a conceptual framework of cool for social marketing through a comprehensive literature review and integrating extant literature on cool. Design/methodology/approach: A comprehensive search and review of extant literature across social marketing, business disciplines, arts, psychology, social sciences and humanities was undertaken to develop an understanding of cool and its relevance to social marketing. The review permitted developing a comprehensive set of characteristics that are associated with cool. Findings: A conceptual framework of cool organised according to the following dimensions is presented and discussed: deviating from norm, self-expressive, indicative of maturity, subversive, pro-social, evasive, and attractive. Originality/value: This paper advances theoretical knowledge in the social marketing domain by offering a conceptual framework of cool, and by suggesting a set of guidelines to develop cool social marketing programs.